KENALI DAN SADARI DIABETES SEJAK DINI: PROGRAM EDUKASI DAN SKRINING KESEHATAN MASYARAKAT DESA MANDALAWANGI, KECAMATAN NAGREG, KABUPATEN BANDUNG - Sri Mas Hartini, Ni Nyoman; Susilawati, Elis; Supriadi, Dadih; Sutoro, Meylani; Lisni, Ida; Priyadi, Akhmad (Batara Wisnu : Indonesian Journal of Community Services, 2025)
Diabetes mellitus is one of the growing public health problems, particularly in rural areas such as Mandalawangi Village, Nagreg Subdistrict, Bandung Regency. Low public awareness of early detection and healthy lifestyle practices has contributed to the increasing prevalence of diabetes. This community service program was carried out using a participatory approach, which included interactive health education, random blood glucose screening, and lifestyle counseling. A total of 78 participants were involved and underwent pre-test and post-test assessments. The results showed that education significantly improved participants’ knowledge, as indicated by a statistically significant difference between pre-test and post-test scores (8.33 vs 8.94; p=0.0058). Screening results revealed that 15.4% of participants were categorized as pre-diabetic and 6.4% as diabetic. The establishment of the *Mandalawangi Healthy Community* serves as a follow-up initiative to ensure the sustainability of the program. Overall, the education and screening activities successfully enhanced community knowledge and awareness about diabetes and provided an important foundation for managing healthy lifestyles and preventing further complications.